2016
DOI: 10.3906/sag-1503-121
|View full text |Cite
|
Sign up to set email alerts
|

Macrolide and lincosamide resistance in staphylococcal clinical isolates in Nablus, Palestine

Abstract: Background/aim: Macrolide and lincosamide antibiotics are used for the treatment of staphylococcal infections, especially for penicillin-allergic patients. In the present study, we evaluate the prevalence of resistance to macrolide and lincosamide antibiotics among staphylococci isolates. Materials and methods:A total of 200 staphylococcal clinical isolates were collected from January 2012 to April 2013. Minimal inhibitory concentrations of erythromycin and clindamycin were determined by agar dilution method. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
2
3
0
Order By: Relevance
“…In contrast, no resistance of CoNS isolate was detected to rifampicin, vancomycin, teicoplanin, nitrofurantoin, linezolid and mupirocin, and very low resistance was detected to tigecycline and moxifloxacin (3.7%, 8.4% respectively). Our findings are in agreement with many studies that showed full activity of most of these aforementioned antimicrobials against clinical CoNS isolates [8,11,13,15].Conversely, many reports from around the world showed different percentage of resistance to vancomycin, teicoplanin and linezolid ranging from 0.8% to 13% [4,12,39]. We think that this zero resistance in this study to glycopeptides and linezolid may be due to its limited prescription and use in Gaza Strip hospitals.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…In contrast, no resistance of CoNS isolate was detected to rifampicin, vancomycin, teicoplanin, nitrofurantoin, linezolid and mupirocin, and very low resistance was detected to tigecycline and moxifloxacin (3.7%, 8.4% respectively). Our findings are in agreement with many studies that showed full activity of most of these aforementioned antimicrobials against clinical CoNS isolates [8,11,13,15].Conversely, many reports from around the world showed different percentage of resistance to vancomycin, teicoplanin and linezolid ranging from 0.8% to 13% [4,12,39]. We think that this zero resistance in this study to glycopeptides and linezolid may be due to its limited prescription and use in Gaza Strip hospitals.…”
Section: Discussionsupporting
confidence: 82%
“…MDR phenotype was detected in 88.9% of CoNS isolates. This high level of MDR in our CoNS collection is similar to many studies conducted in different countries around the world as from China [4], Australia [5], Nigeria [8], Saudi Arabia [10], Jordan [11], Pakistan [12], India [13], West Bank of Palestine [15] and Turkey [40].…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations